The stregth properties of oriented strand board from rubberwood including thickness swelling, water absorption and internal bond / Abdul Rahman Abdul Aziz - Abdul Aziz, Abdul Rahman (2002)
The strength properties of Oriented Strand Board (OSB) from rubberwood were studied to determine the thickness swelling, water absorption and internal bond The OSB sample that use for the test is manufactured for the first time under laboratory condition. The samples of experimental board were test to determine the strength properties of the sample. The thickness swelling and water absorption test give a good result rather than the standard given EN 317,1993. The internal bond testing gives high strength properties, which satisfy the minimum requirements as stipulated in EN 319, 1993. The result value is affected by density of the sample. The high density gives the maximum result rather than the low-density give the minimum result. The verities of density are affected by the sample placing in the panel. The sample were taken in the middle of the panel were give a higher density rather than the sample beside the panel. This study shows the rubberwood has a significant potential to replace the commercial panel OSB with acceptable properties for structural applications.